A new kind of parameter conjugate gradient for unconstrained optimization - Basim Abbas Hassan; Hussein O. Dahawi; Azzam S. Younus (Institute of Advanced Engineering and Science, 2020)
In this paper, a replacement new parameter conjugate gradient for unconstrained optimization. The sufficient descent property cleave to. The global convergence property of the new method is proved under some assumptions. Numerical results explain that the new parameter is superior in practice.